Polysaccharides from Aconitum carmichaelii leaves: Structure, immunomodulatory and anti-inflammatory activities. (1st September 2022) - Fu, Yu-Ping; Li, Cen-Yu; Peng, Xi; Zou, Yuan-Feng; Rise, Frode; Paulsen, Berit Smestad; Wangensteen, Helle; Inngjerdingen, Kari Tvete
Abstract: Roots of Aconitum carmichaelii are used in Asian countries due to its content of bioactive alkaloids. In the production of root preparations, tons of leaves are usually discarded, leading to a huge waste of herbal material. The aim of this study is to investigate the polysaccharides in these unutilized leaves. A neutral polysaccharide (AL-N) appeared to be a mixture of heteromannans, and two purified acidic polysaccharides (AL-I-I and AL-I-II) were shown to be pectins containing a homogalacturonan backbone substituted with terminal β-Xyl p- units. AL-I-I consisted of a type-I rhamnogalacturonan core, with arabinan and type-II arabinogalactan domains while AL-I-II was less branched. AL-N and AL-I-I were able to modulate the complement system, while AL-I-II was inactive. Interestingly, AL-N, AL-I-I and AL-I-II were shown to exert anti-inflammatory effects on porcine enterocyte IPEC-J2 cells. AL-I-I and AL-I-II were able to down-regulate the expression of toll-like receptor 4 (TLR4) and nucleotide-binding oligomerization domain 1 (NOD1). Graphical abstract: Unlabelled Image